Analysis of the methods and trends of money laundering by import – export transactions - Ju. M. Beketnova (Управление)
The article discusses the urgent problem of money laundering. In an effort to circumvent the law and avoid justice, seeking to circumvent the law and avoid justice, criminals resort to a wide variety of ways and methods of money laundering. However, typical patterns or patterns in the organization of shadow financial services schemes can be traced. The study of typologies of money laundering is considered by the international anti-money laundering community as one of the areas that ensure the strategic superiority of state bodies in the fight against this phenomenon.The purpose of the study is to identify trends in money laundering in foreign economic transactions and methods of counteraction. The research method is typological analysis. For a long time, the study of typologies in financial monitoring was of an empirical nature, an attempt was made in this article to systematize and scientifically interpret the accumulated knowledge. The article examines examples of typologies of export-import transactions, including “carousel” commodity schemes, highlights the indicators of this type of money laundering schemes. The regulatory authorities can adopt the research results.